2021
DOI: 10.1371/journal.pone.0241281
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor 9 (FGF9) negatively regulates the early stage of chondrogenic differentiation

Abstract: Fibroblast growth factor signaling is essential for mammalian bone morphogenesis and growth, involving membranous ossification and endochondral ossification. FGF9 has been shown to be an important regulator of endochondral ossification; however, its role in the early differentiation of chondrocytes remains unknown. Therefore, in this study, we aimed to determine the role of FGF9 in the early differentiation of chondrogenesis. We found an increase in FGF9 expression during proliferating chondrocyte hypertrophy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…The cytotoxicity test results for different concentrations of lead acetate in neural pre-induction and induction showed that 100 μ m of lead acetate in the pre-induction and 50 and 100 μ m of lead acetate in the induction of differentiation were toxic and yielded significantly different cytotoxicity results compared to the control group. The results revealed that, at the beginning of differentiation, only high concentrations of lead acetate were toxic; however, as differentiation progressed toward cholinergic neurons, the sensitivity of these cells to lead acetate increased, perhaps indicating the high sensitivity of cholinergic neurons to the neurons produced in pre-induction, and this sensitivity may be attributed to apoptotic mechanisms (Flora et al, 2012) or the replacement of calcium with lead (Wright et al, 2021) and their effect on protein kinase C or interference with NGF-receptor TrkA through protein kinase C phosphorylation and calmodulin-depending kinase with lead, which inhibits the formation and expression of cholinergic cells (Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The cytotoxicity test results for different concentrations of lead acetate in neural pre-induction and induction showed that 100 μ m of lead acetate in the pre-induction and 50 and 100 μ m of lead acetate in the induction of differentiation were toxic and yielded significantly different cytotoxicity results compared to the control group. The results revealed that, at the beginning of differentiation, only high concentrations of lead acetate were toxic; however, as differentiation progressed toward cholinergic neurons, the sensitivity of these cells to lead acetate increased, perhaps indicating the high sensitivity of cholinergic neurons to the neurons produced in pre-induction, and this sensitivity may be attributed to apoptotic mechanisms (Flora et al, 2012) or the replacement of calcium with lead (Wright et al, 2021) and their effect on protein kinase C or interference with NGF-receptor TrkA through protein kinase C phosphorylation and calmodulin-depending kinase with lead, which inhibits the formation and expression of cholinergic cells (Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This analysis showed strong expression of phospho‐ERK1/2 but not phospho‐STAT1, suggesting possible phosphorylation independent STAT1 function in chondrocytes (Krejci et al, 2008). Inhibition of FGF9 promotes the growth and differentiation of ATDC5 chondroprogenitor cells through inhibition of phosphorylation of AKT and glycogen synthase kinase‐3β (GSK3β) (Zhang, Weng, et al, 2021). Inhibition of GSK3β in cultured metatarsal bones increased FGF18 expression and suppressed chondrogenesis through regulation of β‐catenin levels.…”
Section: Selected Topics In Genetics Development Regeneration and Dis...mentioning
confidence: 99%
“…Other upregulated IMM genes were not previously implicated in chondrocyte differentiation, such as those encoding the transcription factors POU3F3 and ZFP703, growth factors CSF1 and PTN, and the Netrin receptor UNC5C (Figures 4A,B, labelled pink; Cecchini et al, 1997;Tare et al, 2002;Srivatsa et al, 2014;Kumar A. et al, 2016;Kumar S. et al, 2016). Upregulated genes in MAT included IFITM5, whose role had only been studied previously in osteoblast differentiation, and many other signalling pathway genes previously implicated in cartilage maturation, including BMP4, FGF9, HES5, TEK, TGFBR2, TGFBR3, WNT5B, and WNT11 (Figures 4A,B, labelled yellow; Hoffmann and Gross 2001;Yang et al, 2003;Karlsson et al, 2010;Shen et al, 2013;Usami et al, 2016;Zhang et al, 2021). Additional genes upregulated in MAT had never been associated previously with chondrocyte maturation, including those encoding the kinase FAM20C and transcription factor TCF7L2 (Hirose et al, 2020;Li et al, 2021).…”
Section: Hh36 Chick Ceratobranchial (See Supplementary Tables S3 S4mentioning
confidence: 93%